Clopidogrel monotherapy is associated with higher mortality risk compared to aspirin: a retrospective analysis of NHANES 1999–2018 - Tieshi Zhu; Yong He; Yuzhang Bei; Hui Mai; Le Zhao (Platelets, 2025)
Background Clopidogrel and aspirin are widely used antiplatelet agents. Although clopidogrel resistance is more prevalent in Asian populations, a Korean study suggested that clopidogrel was superior to aspirin in patients who completed standard dual antiplatelet therapy following percutaneous coronary intervention. However, the comparative effectiveness of clopidogrel versus aspirin in populations with lower levels of clopidogrel resistance remains to be further investigated.Methods This study included 1,007 participants from NHANES 1999–2018 who were receiving aspirin or clopidogrel monotherapy. Cox proportional hazards regression and Kaplan-Meier survival analyses were used to compare the risks of mortality between the two groups. Sensitivity analyses were conducted by excluding individuals who died within the first 6 months of follow-up.Results Across all Cox models, clopidogrel use was associated with significantly higher risks of all-cause mortality (Model 1, HR1.47, 95%CI 1.20–1.79, p < .01; Model 2, HR1.25, 95%CI 1.02–1.54, p = .03; Model 3, HR 1.33, 95%CI 1.08–1.64, p = .01; Model 4, HR1.31, 95%CI 1.06–1.63, p = .01), stroke and cardiac mortality (Model 1, HR1.76, 95%CI 1.27–2.43, p < .01; Model 2, HR1.41, 95%CI 1.01–1.97, p = .04; Model 3, HR 1.54, 95%CI 1.10–2.17, p = .01; Model 4, HR1.47, 95%CI 1.03–2.08, p = .03) compared with aspirin. These associations remained consistent in sensitivity analyses. Kaplan-Meier survival curves also indicated higher risks of all-cause mortality, stroke and cardiac mortality in the clopidogrel group relative to the aspirin group.Conclusion In this community-based population, clopidogrel monotherapy was associated with higher risks of all-cause mortality, stroke and cardiac mortality compared with aspirin.